The effect of external magnetic fields on the catalytic activity of Pd nanoparticles in Suzuki cross-coupling reactions. Issue 15 (4th April 2016) - Gao, Lei; Wang, Changlai; Li, Ren; Li, Ran; Chen, Qianwang
Abstract : MFs have a significant influence on the Suzuki cross-coupling reaction and make the yield of diphenyl increase. Abstract : Pd nanoparticles supported on Co3 [Co(CN)6 ]2 nanoparticles (marked as Pd@Co3 [Co(CN)6 ]2 nanoparticles) were prepared as catalysts for the Suzuki cross-coupling reaction under external magnetic fields (MFs). It is shown that a weak external MF can increase the rate of the Suzuki cross-coupling reaction at room temperature, and with the increase of the strength of external MFs the reaction rate also increased. At 30 °C, the yield was increased by nearly 50% under a 0.5 T external MF after 24 hours compared to that without a MF applied. Theoretical calculations revealed that the adsorption energy changed from −1.07 to −1.12 eV in the presence of MFs, which increased by 5% compared with the absence of MFs, leading to a lower total energy of the adsorption system, which is beneficial to the reaction. From the analysis of the partial density states, it could be seen that the 2p orbital of the carbon atom in bromobenzene and the 4d orbital of the Pd atom overlap more closely in the presence of MFs, which is beneficial for the electron transfer from the Pd substrate to the bromobenzene molecule. This study is helpful in understanding the interaction between MFs and catalysts and regulating the process of catalytic reactions via MFs.